Implementation of Group Guidance Services To Improve Student Understanding About Academic Procrastination - Apri Kasman; Yarmis Syukur; Marlina (International Conference on Education, Islamic Studies and Social Sciences Research)
Currently many of the students are late in completing the study on time, the student likes to procrastinate the task, prefer to play rather than complete the lecture assignment. This shows the student's academic procrastination behavior. With the implementation of group guidance services can reduce student academic procrastination students are expected to no longer experience acadelearnedmic procrastination behavior. The method in this research is quasi experiment. The One Group Pre-test Post-test Design, the subject of this study is a student Stkip PGRI West Sumatra. The result of this research is the implementation of group guidance service can improve the students understanding about academic procrastination